Ln2O3/K2S2O8 Promoted Synthesis of Acetic Acid from Methane and Carbon Monoxide under Mild Conditions - ASADULLAH, Mohammad; TANIGUCHI, Yuki; KITAMURA, Tsugio; FUJIWARA, Yuzo (Journal of The Japan Petroleum Institute, 1998)
The combination of lanthanoid compounds and potassium peroxodisulfate (K2S2O8) has been found to promote the direct formation of acetic acid from methane (40atm) and carbon monoxide (20atm) in trifluoroacetic acid (TFA) at 80°C. The yield of acetic acid was affected strongly by the ligands present with the lanthanoid elements. The ytterbium oxide exhibited higher reactivity than ytterbium sulfide, ytterbium chloride and ytterbium acetate. The sulfide ligand strongly prohibited the formation of acetic acid from carboxylation of methane in TFA. The order of ligands by which acetic acid is formed is oxide>acetate>chloride>sulfide. Of the oxides tested, Yb2O3 and Eu2O3 showed higher activities.